The ethics of human cloning. - Kass, Leon.; Wilson, James Q. (Washington AEI, 1998)
Explores the ethics of human cloning, reproductive technology and the teleology of sexuality from two perspectives which both fundamentally distrust the notion of cloning, but for differing reasons. The volume is intended to inform the public policy debate on permissible genetic research.
Today, biological science is rising on a wall of worry. No other science has advanced more dramatically during the past several decades, nor yielded so many palpable improvements in human welfare. Yet none except nuclear physics has aroused greater apprehensions among the general public and leaders in such diverse fields as religion, the humanities and government. In this volume, Leon R. Kass, a teacher, scientist and humanist, and James Q. Wilson, a political scientist to whom four US presidents have turned for advice on crime, drug abuse, education and other crises in American life, explore the ethics of human cloning, reproductive technology and the teleology of human sexuality. Although in their dialogue, both authors share a fundamental distrust of the notion of human cloning, they base their reticence on different views of the role of sexual reproduction and the role of the family. Professor Kass contends that in vitro fertilization and other assisted reproduction techniques that place the origin of human life in human hands have eroded the respect for the mystery of sexuality and human renewal. Professor Wilson, in contrast, asserts that whether a human life is created naturally or artificially is immaterial as long as the child is raised by loving parents in a two-parent family and is not harmed by the means of its conception. The volume is intended to inform the public policy debate over the permissible conduct of genetic research and the permissible uses of its discoveries.
The wisdom of repugnance
Keywords: Human cloning -- Moral and ethical aspects; Human reproductive technology -- Moral and ethical aspects